1988
DOI: 10.1063/1.100460
|View full text |Cite
|
Sign up to set email alerts
|

Interdiffusion and interfacial reaction between an YBa2Cu3Ox thin film and substrates

Abstract: Interdiffusion and interfacial reaction between a sputter-deposited YBa2Cu3Ox thin film and substrates (MgO, sapphire, quartz, and Si) have been investigated by 2.7 MeV 4He+ Rutherford backscattering spectrometry. The diffusivities of Cu in the substrates and of the substrate elements (Mg, Al, and Si) in the Y-Ba-Cu-O thin films have been determined over the annealing temperature range from 876 to 1226 K in an oxygen atmosphere. Among three metallic elements of Y, Ba, and Cu, Cu diffuses the fastest into the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…2a). Cu diffusion from YBCO into the film substrate has been previously reported by Nakajima et al [28] on Cu diffusion into single crystal MgO. The diffusional profile which corresponds to the raw data shown in Fig.…”
Section: Sims Measurementsmentioning
confidence: 86%
“…2a). Cu diffusion from YBCO into the film substrate has been previously reported by Nakajima et al [28] on Cu diffusion into single crystal MgO. The diffusional profile which corresponds to the raw data shown in Fig.…”
Section: Sims Measurementsmentioning
confidence: 86%
“…Post annealing at 800 °C of amorphous and insulating 123 films on silicon yields heavily reacted samples, as reported in the literature [23,24]. Nakajima et al [24] reported the formation of copper silicide.…”
Section: Direct Deposition Of 123 On Si and Sio Ementioning
confidence: 49%
“…Nakajima et al [24] reported the formation of copper silicide. In a powder mixture of silicon and the superconducting 123 phase, the 211 Y-Ba-Cu-O phase was observed primarily after annealing between 600 and 800 °C in an oxygen flow by Cheung and Ruckenstein [25].…”
Section: Direct Deposition Of 123 On Si and Sio Ementioning
confidence: 99%
See 1 more Smart Citation
“…SrTi03, MgO, YZS) (see for example [6] and references therein). This is mainly due to the interdiffusion between film and sapphire [15], which takes place at high temperatures, and to the mismatch of the lattice parameters of Y-Ba-Cu-O and A1203.…”
mentioning
confidence: 97%